Gaya Hidup Konsumtif dan Dampaknya terhadap Motivasi Belajar Mahasiswa Tadris IPS UIN Sayyid Ali Rahmatullah Tulungagung - Elif Hakiki Wahyudiana; Dita Hendriani (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2024)
Social change among teenagers today needs to be a common focus so as not to damage culture. Teenagers are the determinants of the fate of the nation. Brilliant teenagers are teenagers who are not eroded by the current of negative social change. This research aims to determine the relationship between consumer lifestyles and their impact on the learning motivation of students at UIN Sayyid Ali Rahmatullah Tulungagung. Consumptive behavior is a form of social change that is widely experienced by teenagers in the transitional age towards adulthood, so it is important for humans today to suppress the problem of negative impacts caused by social change. Various findings of information collected from students as respondents and which have been processed by researchers have resulted in input that consumer behavior increases motivation or enthusiasm for learning because by excessively and impulsively subscribing to goods or services, it creates satisfaction and happiness in itself, plus the large number of stalls available, thus making things easier for respondents. Consumptive attitudes are added to by the desire of students who want to keep up with the times by buying the latest fashion..